Self-assembled soft nanoparticle membranes with programmed free volume hierarchy - Wu, Jia-Kai; Wang, Nai-Xin; Hung, Wei-Song; Zhao, Qiang; Lee, Kueir-Rarn; An, Quan-Fu (Journal of materials chemistry. A, Materials for energy and sustainability, 2018)
Pore hierarchy in polymers is crucial for applications spanning nano-medicine, sustainable energy, and molecular separation. However, polymer free volume hierarchy with ultra-fine sizes (<5 Å) and modularity remains an important but elusive subject of research due to the dynamic, transient and random nature of free volume cavities. Here we show the construction of hierarchical free volume through the self-assembly of structured polyelectrolyte complex nanoparticles (∼40 nm) in the vacuum filtration process. Membranes with tunable thickness and well-defined nanoparticle structures are prepared, featuring enhanced mechanical strength, flexibility, and more importantly, programmed free volume consisting of intra-particle ( r 1 = 3.22 Å) and inter-particle ( r 2 = 4.45 Å) cavities. Both free volume elements are effectively tuned and the collective fractional free volume is improved 8 times, leading to membrane molecular channels outperforming other polymer membranes in pervaporation dehydration of ethanol.